Involving Family Members in the Delivery of TB Care in the Kandy District, Sri Lanka - Jayawardena, KAS; Medagedara, D (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2010)
Objective : To determine the effectiveness of using family members in the delivery of Directly Observed Treatment (DOT) in a local community, Sri Lanka Method : Thirty nine TB patients detected at the Chest Clinic, Kandy between 1st of September and 31st of December 2007 were given DOT using family members (study group). Treatment outcome of the study group was evaluated in December 2008 and compared with the outcome of 42 patients, who had undergone DOT at peripheral health centres during the same period. Results : Sputum conversion rate at the end of the intensive phase of treatment of the study group was 95% and the rate of comparison group was 88%. Treatment was successfully completed in 95% of patients in the study group and 86% of patients in the comparison group. No defaulters were found in the study group whereas 4 defaulters were in the comparison group. Observed outcome differences between two groups were not statistically significant (p > 0.05). Conclusion : The present study reveals that the treatment outcome is good among patients who receive family DOT. The important prerequisites to ensure successful family DOT include correct selection of patients and DOT providers, giving adequate instruction for treatment adherence, and monitoring of the progress. Keywords : DOTS; family DOT; Sri Lanka DOI: 10.3126/saarctb.v6i1.3059 SAARC J. Tuber. Lung Dis. HIV/AIDS 2009 VI (1) 12-15